Characterization of microsatellite loci in Tilia platyphyllos (Malvaceae) and cross‐amplification in related species1. (28th March 2013) - Phuekvilai, Prattana; Wolff, Kirsten
Abstract : Premise of the study: Microsatellite markers in the genus Tilia were developed to investigate the genetic variation in T. platyphyllos and its relationship with T. cordata . Methods and Results: Fifteen microsatellite markers were developed using a microsatellite enrichment protocol. Most loci show a high level of polymorphism in two T. platyphyllos populations from France. The number of alleles ranged from one to 15, with a mean of 8.96. The mean observed and expected heterozygosities were 0.71 and 0.70, respectively. Cross‐amplification results indicated that 12 out of 15 loci amplified polymorphic loci in 23 species in the genus. Conclusions: These markers will be useful tools for investigating the phylogeography and hybridization of Tilia species.